A hierarchical origami moisture collector with laser-textured microchannel array for a plug-and-play irrigation system. Issue 9 (5th February 2021) - Tang, Xiaoxuan; Liu, Hongwei; Xiao, Lin; Zhou, Maolin; Bai, Haoyu; Fang, Jiahao; Cui, Zehang; Cheng, Hui; Li, Guoqiang; Zhang, Yabin; Cao, Moyuan
Abstract : Inspired by the Triarrhena sacchariflora, a hierarchical origami moisture collector was designed to achieve the highly-efficient fogdrop harvesting and long-lasting moisture retention forplant irrigation without an external energy input. Abstract : Bioinspired functional structures or devices show great potential for harvesting water resources in the atmosphere. Despite the great advances made in the capture and transportation of the droplets, the efficient storage of harvested water for direct and cyclable utilization is rarely concerned towards real daily life. Inspired by the long-stem storage of water caused from the Triarrhena sacchariflora leaf sheath, a wearable fogdrop collector was developed via laser structuring and origami techniques for effectively nourishing the plants in a lower-evaporation condition. The collector shows an annular thin-wall with a superhydrophilic grooved inwall (SGI), and a circular array of spine with thorns and gradient channels (STGCs). These structural features enable the collector to capture fogdrop by STGC, and keep water inside the thin-wall for long-lasting moisture retention. Furthermore, due to the excellent flexibility and composability, multiple collectors can be easily assembled to a larger harvesting one, implying its scalability potential. The assembled devices show a higher collection efficiency and lower evaporation than the individual ones, reaching ∼8.4 mL per hour when using triple collectors. More interestingly, such devices can be directly used for the moisture retention of the fresh flower, showing water retention of more than 140 min, which is superior to the traditional watering or water spraying. This work gives a flexible design strategy of a portable scalable collector for water harvesting, and especially opens an avenue to the direct and actual utilization of the fogdrop collectors for the flower moisture retention and even agricultural irrigation.